1984
DOI: 10.1073/pnas.81.14.4409
|View full text |Cite
|
Sign up to set email alerts
|

Tumor promoters induce a specific morphological signature in the nuclear matrix-intermediate filament scaffold of Madin-Darby canine kidney (MDCK) cell colonies.

Abstract: Tumor promoters such as phorbol 12-tetradecanoate 13-acetate (TPA), mezerein, teleocidin, aplysiatoxin, and benzoyl peroxide, although structurally unrelated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 26 publications
3
26
1
Order By: Relevance
“…While in SMMC-7721 cells induced with HMBA, the nuclear matrix filaments and intermediate filaments interweaved into a regular and well-distributed meshwork in which the quantity of single filaments increased and differed in slender and thick form, moreover, the nuclear matrix filaments and intermediate filaments firmly fastened to the thin and compact fiber-like nuclear lamina. This morphology of NM-IF system was significantly different from those of rapidly proliferating SMMC-7721 cells but similar to those of some previously reported epithelial or normal cells [15,18] , and was consistent with our previous studies in which we treated the human osteosarcoma cell line MG-63 and human gastric adenocarcinoma cell line MGC80-3 with retinotic acid (RA) respectively [12,19] . It showed that the morphology and function of NM-IF system in SMMC-7721 cells during its differentiation had undergone a reverse alteration.…”
Section: Smmc-7721supporting
confidence: 78%
“…While in SMMC-7721 cells induced with HMBA, the nuclear matrix filaments and intermediate filaments interweaved into a regular and well-distributed meshwork in which the quantity of single filaments increased and differed in slender and thick form, moreover, the nuclear matrix filaments and intermediate filaments firmly fastened to the thin and compact fiber-like nuclear lamina. This morphology of NM-IF system was significantly different from those of rapidly proliferating SMMC-7721 cells but similar to those of some previously reported epithelial or normal cells [15,18] , and was consistent with our previous studies in which we treated the human osteosarcoma cell line MG-63 and human gastric adenocarcinoma cell line MGC80-3 with retinotic acid (RA) respectively [12,19] . It showed that the morphology and function of NM-IF system in SMMC-7721 cells during its differentiation had undergone a reverse alteration.…”
Section: Smmc-7721supporting
confidence: 78%
“…Furthermore, nuclear matrix proteins have been implicated in malignant transformation (18,19), such as alterations in DNA ploidy, DNA content, nuclear shape, and proliferative states (20). The nuclear matrix protein, termed NRP/B (ENC-1), is expressed abundantly in the nervous system (21,22), and its expression has been observed in various brain cell lines, human brain tumors (23,24), and hairy cell leukemia (25).…”
Section: Introductionmentioning
confidence: 99%
“…These proteins have been implicated in malignant transformation (Fey and Penman, 1984;Getzenberg et al, 1996), such as alterations in DNA ploidy, DNA content, nuclear shape and proliferative states (Berezney et al, 1995). The nuclear matrix protein termed nuclear restricted protein in brain (NRP/B) (Kim et al, 1998), also known as ENC-1 (Hernandez et al, 1997), was characterized as a Kelch-related protein.…”
Section: Introductionmentioning
confidence: 99%